An intelligent prediction of CO2 leakage in underground geological storage sites - Guanliang Zhang; Haoxian Liu; Tao Yang; Zejun He; Lu Zhang; Jiajun Fu; Jiancheng Niu; Farshad Sadeghpour; Mehdi Ostadhassan; Mengdi Sun (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Contrasting mechanical evolution of bakken shale under hydrous and anhydrous pyrolysis: A nanoindentation-based assessment - Mengdi Sun; Jiajun Fu; Yeping Ji; Yiquan Ma; Bo Liu; Qiuli Huo; Aydin Larestani; Abdolhossein Hemmati-Sarapardeh; Mehdi Ostadhassan (International Journal of Rock Mechanics and Mining Sciences, 2026)

3D reconstruction of pore throat connectivity in Shale: An SAXS-MICP integrated framework - Linhao Zhang; Shu Jiang; Jiale Fu; Fei Xie; Zhile Han; Zihao Li; Mengdi Sun (Marine and Petroleum Geology, 2025)

Water vapor sorption behavior of shale organic matter with various types and maturation - Jiajun Fu; Ke Xu; Yeping Ji; Xuezhe Wang; Yiquan Ma; Mehdi Ostadhassan; Zhejun Pan; Duo Wang; Bo Liu; Yubing Ke; Mengdi Sun (Journal of Hydrology, 2025)

Multifactor synergistic drivers of first arrival dates in Chinese birds: Nationwide evidence from audio-video fusion monitoring - Mengdi Fu; Hongchang Wang; Haifang Jian; Yuanyuan Zhang (Journal of Environmental Management, 2025)

Dual-coated Akkermansia muciniphila for the treatment of inflammatory bowel disease - Peixu Zhao; Guangshuai Zhang; Hongge Wang; Xiaolang Luo; Mengdi Qin; Manlin Teng; Genyang Ye; Zhaohua Li; Qiang Fu (Chemical Engineering Journal, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

scSAGRN: Inferring gene regulatory networks from single-cell multi-omics using spatial association - Qing Ren; Mengdi Nan; Yuhan Fu; Xiang Chen; Yibing Ma; Yongle Shi; Jie Gao (BioSystems, 2025)

Visualization study of multiphase flow in deep-sea mining based on dual-modality electrical tomography - Xuanhe Han; Yanlian Du; Mengdi Fu; Jingyu Zhu; Rongqian Ruan; Yijun Shen (Ocean Engineering, 2025)

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

A fully Coupled thermal-hydrodynamic–chemical numerical model for simulating gas hydrate-bearing sediments dissociation based on peridynamic differential operator method - Linfeng Zhang; Guorong Wang; Zhiyuan Li; Lin Zhong; Qiang Fu; Jiwei Wu; Mengdi Wu; Dongmei Liang; Yuhang Zheng (Computers and Geotechnics, 2025)

Particle size is an important factor influencing the effects of biochar return to woodland soils: An evaluation from the perspective of sapling growth and soil microbial carbon processes - Xiaoyu Gao; Haoting Liu; Wenxuan Mei; Wenwen Zhang; Haoyu Dong; Xiaohua Fu; Mengdi Xie; Yujie Han; Lei Wang (Journal of Environmental Management, 2024)

An improved convolutional architecture for quantitative characterization of pore networks in fine-grained rocks using FIB-SEM - Bo Liu; Qamar Yasin; Mengdi Sun; Atif Ismail; David A. Wood; Xin Tian; Baiquan Yan; Li Fu (International Journal of Coal Geology, 2024)

Estuarine wetland tidal organic carbon activates microbial carbon pump and increases long-term soil carbon stability - Mengdi Xie; Haoyu Dong; Xiaolu Tang; Liwei Qian; Wenxuan Mei; Jianfang Yan; Xiaohua Fu; Yu Hu; Lei Wang (CATENA, 2024)

Automatic pore structure analysis in organic-rich shale using FIB-SEM and attention U-Net - Qamar Yasin; Bo Liu; Mengdi Sun; Ghulam Mohyuddin Sohail; Atif Ismail; Mariusz Majdanski; Naser Golsanami; Yan Ma; Xiaofei Fu (Fuel, 2024)

Thiol-modified hyaluronic acid improves the physical stability of curcumin-zein nanoparticles by forming disulfide bonds with zein - Guangshuai Zhang; Mengdi Qin; Mengran Guo; Mo Li; Di Zhang; Yichi Sun; Bingyang Liu; Zhonggui He; Qiang Fu (Food Chemistry, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Preparation and characterization of novel composite nanoparticles using zein and hyaluronic acid for efficient delivery of naringenin - Genyang Ye; Tianlong Wu; Zhaohua Li; Manlin Teng; Lixue Ma; Mengdi Qin; Peixu Zhao; Qiang Fu (Food Chemistry, 2023)

Cadmium stimulated cooperation between bacterial endophytes and plant intrinsic detoxification mechanism in Lonicera japonica thunb - Mengdi Xie; Xiaoyu Gao; Saiwei Zhang; Xiaohua Fu; Yiquan Le; Lei Wang (Chemosphere, 2023)

Environmental risks of antibiotic resistance genes released from biological laboratories and its control measure - Xiaoyu Gao; Xiaohua Fu; Mengdi Xie; Lei Wang (Environmental Monitoring and Assessment, 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

Recent advances in tissue stem cells - Xin Fu; Qiang He; Yu Tao; Mengdi Wang; Wei Wang; Yalong Wang; Qing Cissy Yu; Fang Zhang; Xiaoyu Zhang; Ye-Guang Chen; Dong Gao; Ping Hu; et al. (Science China Life Sciences, 2021)

Modeling leaf senescence of deciduous tree species in Europe - Qiang Liu; Shilong Piao; Matteo Campioli; Mengdi Gao; Yongshuo H. Fu; Kai Wang; Yue He; Xiangyi Li; Ivan A. Janssens (Global Change Biology, 2020)
Autumnal leaf senescence signals the end of photosynthetic activities in temperate deciduous trees and consequently exerts a strong control on various ecological processes. Predicting leaf senescence dates (LSD) with high accuracy is thus a prerequisite for better understanding the climate–ecosystem interactions. However, modeling LSD at large spatial and temporal scales is challenging. In this study, first, we used 19972 site‐year records (848 sites and four deciduous tree species) from the PAN European Phenology network to calibrate and evaluate six leaf senescence models during the period 1980–2013. Second, we extended the spatial analysis by repeating the procedure across Europe using satellite‐derived end of growing season and a forest map. Overall, we found that models that considered photoperiod and temperature interactions outperformed models using simple temperature or photoperiod thresholds for Betula pendula , Fagus sylvatica and Quercus robur . On the contrary, no model displayed reasonable predictions for Aesculus hippocastanum . This inter‐model comparison indicates that, contrary to expectation, photoperiod does not significantly modulate the accumulation of cooling degree days (CDD). On the other hand, considering the carryover effect of leaf unfolding date could promote the models’ predictability. The CDD models generally matched the observed LSD at species level and its interannual variation, but were limited in explaining the inter‐site variations, indicating that other environmental cues need to be considered in future model development. The discrepancies remaining between model simulations and observations highlight the need of manipulation studies to elucidate the mechanisms behind the leaf senescence process and to make current models more realistic.

Functional zoning and space management of Three-River-Source National Park - Mengdi Fu; Junliang Tian; Yueheng Ren; Junsheng Li; Weiwei Liu; Yanpeng Zhu (Journal of Geographical Sciences, 2019)